Sudden and Prevalent Deaths of Foraging Honey Bees in Early Spring During Sowing of Clothianidin Coated Maize Seeds Between 2013 and 2018 in Turkey - Oruç, Hasan H.; Çayci, Meltem; Sariyev, Rashad (Journal of Apicultural Science, 2020)
Between 2013 and 2018, there was an outbreak of sudden foraging honey bee deaths in Turkey’s Çukurova Region from the beginning of February to the middle of March, a period of time when the sowing of maize seeds occurs in the region. Upon returning, the affected bees were unable to enter the hive because of unbalanced flying and walking. Deaths were seen at apiaries located on plains or near plains where maize seeds were sowed. When winds blew from the direction of the plains towards the hives, honey bee deaths increased, but when the weather was rainy, honey bee deaths decreased or stopped. Honey bee losses were mainly between 30% and 80%. Investigations related to the honey bee deaths were carried out in the affected apiaries using on-site inspection and laboratory tests. The main reason of deaths would be linked to the clothianidin coated maize seeds used in the plain during sowing period. No remarkable correlation with any bee pathogens was detected related to the sudden and prevalent honey bee deaths.